PROGRAM KEMITRAAN MASYARAKAT STIMULUS (PKMS) UNTUK MENINGKATKAN PRODUKTIVITAS PRODUK TEMPE TRADISIONAL DI KELURAHAN MARGAHAYU, KECAMATAN BEKASI TIMUR, KOTA BEKASI - Andi Muhammad Sadli; Budi Rachmawati; Reni Yesi S. (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
Tempe production continues to grow in line with community needs as it is affordable and highly nutritious. The Community Partnership Stimulus Program (PKMS) – PMP aims to support micro-business groups in Margahayu Village, Bekasi, by providing appropriate technology, particularly an energy-efficient soybean hulling machine. The implementation showed significant efficiency improvements. Before using the machine, producing Tempe from 5 kg of soybeans required 6 minutes 45 seconds, while after implementation it only took 3 minutes 15 seconds, saving 3 minutes 30 seconds. Electricity costs also became more efficient: previously, Rp50,000 was enough for 23 days, but after using the machine, the same cost could last up to 20 days with higher productivity. Evaluation results indicated an increase in net monthly income of Rp1,200,000, which positively impacts partners’ livelihoods. Overall, the machine improved efficiency in both production time and electricity usage, while producing better quality Tempe with longer durability